A narrative medicine intervention in pediatric residents led to sustained improvements in resident well-being. (31st December 2023) - Bajaj, Nimisha; Phelan, James; McConnell, Erin E.; Reed, Suzanne M.
Abstract: Background: Burnout in pediatric residents is widespread. Certain factors are associated with decreased burnout, such as empathy, self-compassion, mindfulness, and resilience, while perceived stress is associated with increased burnout. Narrative medicine may reduce burnout by its impact on protective and exacerbating factors and can be an active tool to promote wellness. The objective of this pilot study was to evaluate immediate and delayed benefits of a longitudinal narrative medicine intervention for pediatric residents using qualitative and quantitative measures. Materials and Methods: We designed a voluntary longitudinal narrative medicine intervention implemented via Zoom teleconferencing software over five months for pediatric residents at Nationwide Children's Hospital. It consisted of six one-hour long sessions where residents engaged with literature, responded to a writing prompt, and shared their reflections. It was evaluated using open-ended survey questions and established quantitative assessment tools of well-being with validity evidence. Results were compared before the intervention, immediately after, and six months later using one-way ANOVA and multiple linear regression. Qualitative data was analyzed using thematic analysis. Results: Twenty-two (14% of eligible) residents participated in at least one session. After the intervention, the following themes emerged for benefits to resident well-being: the ability to Build Community, have an Outlet for Self-Expression, reap Emotional and Mental Health Benefits, and work on Personal Growth . Benefits were sustained even six months later, which has not been shown previously. While there were significant qualitative findings, between all three time points, there was no change in any quantitative well-being measures. Conclusion: Our longitudinal narrative medicine pilot study showed meaningful sustained qualitative benefits, though no quantitative changes, in measured well-being outcomes that have been previously associated with lower resident burnout. While not a panacea, narrative medicine can be a useful strategy for residency programs to improve pediatric resident well-being even after completion of planned interventions. Key Message: We used a mixed-methods approach to assess the effects of a longitudinal narrative medicine intervention on well-being in pediatric residents. Open-ended responses indicated that residents found utility in and appreciated the intervention and experienced sustained improvements in their mental and emotional health, though the sample size was likely too small to show quantitative changes in well-being measures. Narrative medicine is not a panacea, but it can be a useful tool to provide to pediatric residents to promote sustained improvements in their well-being through the framework of relationship-centered care.